2020
DOI: 10.1002/oa.2947
|View full text |Cite
|
Sign up to set email alerts
|

Tracing craniovascular traits in artificially modified pre‐Columbian crania from Cuba, the largest Caribbean archipelago

Abstract: The impressions left by the vascular system on the surface of the skull, like those of the middle meningeal vessels, the dural venous sinuses, and the emissary veins, are a unique source of vascular and anatomical evidence when working with osteological collections, as is the case with bioarchaeological, forensic, and paleoanthropological investigations. Craniovascular features have been investigated in multiple modern human populations; however, no information is available on their analysis in artificially mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In the present study, we found only minor differences between the skulls with and without ACM in craniovascular morphology relating to the sizes of cranial foramina (slightly smaller in skulls with ACM, especially the mastoid foramina). When comparing the current results with other studies (Dean, 1995;O'Loughlin, 1996;Ossenberg, 1970;Rangel-de L azaro, 2021), the different outcomes are not likely to be due to the different statistical power. Our sample size (N = 24) is, in fact, similar to or larger than the sample sizes of the former studies (Ossenberg, 1970: N = 29;Dean, 1995: N = 6;O'Loughlin, 1996: N = 17;Rangel-de L azaro, 2021: N = 8).…”
Section: The Effect Of Cranial Size and Artificial Cranial Modificati...mentioning
confidence: 61%
See 3 more Smart Citations
“…In the present study, we found only minor differences between the skulls with and without ACM in craniovascular morphology relating to the sizes of cranial foramina (slightly smaller in skulls with ACM, especially the mastoid foramina). When comparing the current results with other studies (Dean, 1995;O'Loughlin, 1996;Ossenberg, 1970;Rangel-de L azaro, 2021), the different outcomes are not likely to be due to the different statistical power. Our sample size (N = 24) is, in fact, similar to or larger than the sample sizes of the former studies (Ossenberg, 1970: N = 29;Dean, 1995: N = 6;O'Loughlin, 1996: N = 17;Rangel-de L azaro, 2021: N = 8).…”
Section: The Effect Of Cranial Size and Artificial Cranial Modificati...mentioning
confidence: 61%
“…When comparing the current results with other studies (Dean, 1995;O'Loughlin, 1996;Ossenberg, 1970;Rangel-de L azaro, 2021), the different outcomes are not likely to be due to the different statistical power. Our sample size (N = 24) is, in fact, similar to or larger than the sample sizes of the former studies (Ossenberg, 1970: N = 29;Dean, 1995: N = 6;O'Loughlin, 1996: N = 17;Rangel-de L azaro, 2021: N = 8). The different results may be due to several factors, both genetic and epigenetic, possibly associated with diverse cultural practices of ACM.…”
Section: The Effect Of Cranial Size and Artificial Cranial Modificati...mentioning
confidence: 61%
See 2 more Smart Citations
“…One of these institutions was the Anthropological Museum Montané, founded on June 29, 1903, in Havana, Cuba (Rangel Rivero, 2012. Since then, the Museum Montané has become an essential institution for anthropological and archaeological research in the region (Dacal Moure & Rivero de la Calle, 1986;Dacal Moure & Watters, 2005;Rangel-de Lázaro, 2020). The collections held by the Museum Montané are the result of more than a century of continuous work of professionals, antiquarians, and amateurs.…”
Section: Introductionmentioning
confidence: 99%